A cross-sectional study on risk factors, symptoms, treatment and management strategies of lung cancer in a tertiary care cancer hospital of Bangladesh - Pial, Sazia Afrin (BRAC University, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.